Challenging the Public : Feminism, Law, and Public Policy - Boyd, Susan B. (University of Toronto Press, 1997)
Feminist scholars in disciplines ranging from law to geography challenge our traditional notion of a public/private divide in legal and public policy in Canada and internationally.